2020
DOI: 10.1002/cac2.12108
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐mediated posttranslational modifications and reprogramming of energy metabolism in cancer

Abstract: Altered metabolism is a hallmark of cancer, and the reprogramming of energy metabolism has historically been considered a general phenomenon of tumors. It is well recognized that long noncoding RNAs (lncRNAs) regulate energy metabolism in cancer. However, lncRNA-mediated posttranslational modifications and metabolic reprogramming are unclear at present. In this review, we summarized the current understanding of the interactions between the alterations in cancer-associated energy metabolism and the lncRNA-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
269
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(270 citation statements)
references
References 91 publications
1
269
0
Order By: Relevance
“…13 There is accumulating evidence suggesting that dysregulation of lncRNAs is involved in human cancers, including HCC. [14][15][16] Lnc-Sox4 promotes early tumorigenesis in liver cells through the Stat3-Sox4 pathway 11 ; the lncRNA HULC promotes liver-cancer progression by inhibiting PTEN via miR-15a 17 ; and the lncRNA MCM3AP-AS1 promotes HCC through the miR-194-5p/FOXA1 axis and is associated with poor clinical outcomes in patients with HCC. 18 CNV in lncR-NAs such as focally amplified lncRNA on chromosome 1 (FAL1) affects lncRNA expression and can predict tumor prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 There is accumulating evidence suggesting that dysregulation of lncRNAs is involved in human cancers, including HCC. [14][15][16] Lnc-Sox4 promotes early tumorigenesis in liver cells through the Stat3-Sox4 pathway 11 ; the lncRNA HULC promotes liver-cancer progression by inhibiting PTEN via miR-15a 17 ; and the lncRNA MCM3AP-AS1 promotes HCC through the miR-194-5p/FOXA1 axis and is associated with poor clinical outcomes in patients with HCC. 18 CNV in lncR-NAs such as focally amplified lncRNA on chromosome 1 (FAL1) affects lncRNA expression and can predict tumor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lncRNAs exert regulatory functions in human disease development by binding to microRNAs (miRNAs) and suppressing miRNA‐mediated gene silencing 13 . There is accumulating evidence suggesting that dysregulation of lncRNAs is involved in human cancers, including HCC 14–16 . LncSox4 promotes early tumorigenesis in liver cells through the Stat3‐Sox4 pathway 11 ; the lncRNA HULC promotes liver‐cancer progression by inhibiting PTEN via miR‐15a 17 ; and the lncRNA MCM3AP‐AS1 promotes HCC through the miR‐194‐5p/FOXA1 axis and is associated with poor clinical outcomes in patients with HCC 18 .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs, with over 200 nucleotides in length and involved in diverse gene regulation, account for a large number of ncRNAs (74). Various studies have verified that lncRNAs play a vital role in transcription processes, regulation of cellular contexts, assembly of protein, tumor suppressor dysregulation, and other crucial biological function (75)(76)(77)(78)(79)(80). LINC00673, located on chromosome 17q24.3, has been reported as an oncogene in diverse cancers (81)(82)(83).…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…Initially, lncRNAs were regarded as a transcriptional "noise" and were not considered to have biological functions, but then found that they were involved in the regulation of protein coding genes at both transcriptional and epigenetic level [10]. Up to now, more and more evidences have shown that lncRNAs are widely expressed in most organs and tissues, and participate in various cellular biological processes, including regulating transcription and protein activity, exertion of structural or histological roles, altering RNA processing and expression regulation as pre-cursors of microRNAs, and participating in chromosomal silencing and modification, etc., which mediate the growth of cancer cells reproductive, invasive and apoptotic processes [11][12][13][14]. HOX transcript antisense RNA (HOTAIR) [15], maternal expressed gene 3 (MEG3) [16], urothelial cancer associated factor 1 (UCA1) [17], cancer susceptibility candidate 9 (CASC9) [18], small nucleolar RNA host gene 6 (SNHG6) [19], plasmacytoma variant translocation 1 (PVT1) [20], and HOXA transcript at the distal tip (HOT-TIP) [21] were all confirmed to be abnormally expressed in EC.…”
Section: Introductionmentioning
confidence: 99%